CHALLENGES AND PROSPECTS IN TEACHING THE UZBEK LANGUAGE TO FOREIGN STUDENTS - Dilfuza Pulatova (Modern American Journals, 2025)
This article explores the current challenges and future prospects in teaching the Uzbek language to foreign students, with a focus on the higher education context in Uzbekistan. The growing interest in Uzbek as a foreign language, driven by increased international mobility and Uzbekistan’s expanding diplomatic, cultural, and economic presence, necessitates a reevaluation of pedagogical approaches and curriculum development. The study examines issues such as the lack of standardized teaching materials, limited teacher training in the methodology of teaching Uzbek as a foreign language, and the influence of students’ native language backgrounds. At the same time, it highlights promising developments such as the integration of digital technologies, the emergence of research-based instruction models, and the potential of international academic collaboration. Drawing on both qualitative and comparative analysis, the article offers a critical assessment of current practices and outlines directions for innovation and reform.
Keywords: Uzbek language, foreign language instruction, higher education, language acquisition, teaching methodology, international students, linguistic competence, digital pedagogy, curriculum development.